若m×m+n×n-6n+4m+13=0,则m×m-n×n=?
2个回答
由m×m+n×n-6n+4m+13=0 得
(m×m+4m+4)+(n×n-6n+9)=0 得
(m+2)^2+(n-3)^2=0 得
m=-2
n=3
所以 m^2-n^2=4-9=-5
相关问题
若(m+n)(m-n)²-mn(m+n)=(m+n)×M ,则M的值是?
(m+n)×(m-n)+(m-n)=0怎么做
用“>”“<”或“=”号填空:若m<0,n>0,且|m|>|n|,则m×n=
计算 n/m×(-1/m×根号下n³/m³)
已知m2+ n2+2m-6n+10=0,则m×n= .
问一道数学题thanks啦已知m×m+2mn=384,3mn+2n×n=560,那么2m×m+13mn+6n×n-114
计算下列分式 n/m×(-1/m×根号下n³/m³) m和n都大于0
若m,n是有理数,且3m+n-2+2(√7)×m-(√7)×n+3√7=0,求m,n的值.
若m,n是有理数,且3m+n-2+2(√7)×m-(√7)×n+3√7=0,求m,n的值.
计算 m+n/m²-mn÷(m+n)×(m²-n²)